Determinants of 3Rs behaviour in plastic usage: A study among Malaysians. Issue 12 (December 2020) - Chun T'ing, Loh; Moorthy, Krishna; Yoon Mei, Chin; Pik Yin, Foo; Zhi Ying, Wong; Wei Khong, Chin; Zhao Chern, Gan; Zin Lin, Thong
Abstract: This research was conducted to explore the factors affecting Malaysians' application of reduce, reuse and recycle (3Rs) concept in plastic usage. This study adopted variables from the Theory of Planned Behaviour (TPB), namely, attitude, subjective norm and perceived behavioural control and added on two more variables, habit and facilitating conditions to study the plastic usage. Self-administered questionnaires were used to collect the data and analysis done. The results showed that all variables influence the plastic usage behaviour. This research contributes to a better understanding of the relationship between the determinants of behavioural intention of 3Rs application on plastic usage. Through the suggestions of suitable strategies, this research would contribute to reducing environment pollution caused by plastic waste. Abstract : Plastic waste; Theory of Planned Behaviour (TPB); habit; facilitating conditions; reduce, reuse; and recycle (3Rs); Malaysia